The Effect of Time Scarcity Promotion, Shopping Motives and E-WoM on Impulse Buying Behavior of Shopee Consumers in Manado City - Ahmad, Yavi N.; Mandey, Silvya L.; Pandowo, Merinda HC (Research Parks Publishers, 2023)
This study aims to identify and analyze the effect of Time Scarcity Promotion, Hedonic Shopping Motives, Utilitarian Shopping Motives and E-WoM on Impulse Buying behavior. The number of samples in this study was 100 respondents, collecting data using a questionnaire. The quantitative analysis method used is validity, reliability, classical assumptions and multiple regression using the SPSS 25 application. Shopee is an E-Commerce platform that offers a variety of attractive programs to attract more consumers. Along with the progress of E-Commerce, Impulse Buying behavior in society has developed. The results of the study show that simultaneously Time Scarcity Promotion, Hedonic Shopping Motives, Utilitarian Shopping Motives and E-WoM have a positive and significant effect on Impulse Buying behavior. Then partially each variable Time Scarcity Promotion, Hedonic Shopping Motives, Utilitarian Shopping Motives has a positive and significant effect on Impulse Buying behavior, while E-WoM partially has a positive and insignificant effect.